Performance Tuning of Tile Matrix Decomposition - Suzuki, Tomohiro (2019 IEEE 13th International Symposium on Embedded Multicore/Many-core Systems-on-Chip (MCSoC), 2019)
Task parallel algorithms have attracted attention as algorithms for highly parallel architectures in recent years. The aim of such algorithms is to keep all computing resources running without stalling by executing a large number of fine-grained tasks asynchronously while observing data dependencies. The tile algorithm of matrix decomposition of dense matrices is implemented using a task parallel programming model following such an approach. In this article, we will consider how to select tile size, which is an important performance parameter.